China’s shipping emissions governance: status and prospects under the dual carbon goal - Mai Hu; Yue Dong (Frontiers in Marine Science, 2024)
In the context of the global response to climate change, the shipping industry is facing unprecedented pressure and challenges to reduce emissions. Under the unified leadership of International Maritime Organization (IMO), the international community has begun to take actions to promote the development of the shipping industry in a more environmentally friendly and sustainable direction. As an IMO category (a) member, China is promulgating a series of emission reduction policies to guide the green transformation of its shipping industry. This study first examines China’s recent shipping emission reduction policy post “dual carbon” proposal, assessing its key focus and the current efficacy of China’s shipping emission reduction governance. Based on this, the study examines the challenges China face in reducing shipping emissions. By drawing on global emission reduction practices, we suggest policy measures for China to enhance its efforts and help the shipping industry move towards achieving net-zero emissions.